Understanding the Complexity of Conflict Trauma: A Systematic Review - Abbasi , Khaula (South Asian Journal of Social Sciences and Humanities, 2022)
One of the most serious repercussions of war is the influence it has on the mental health of individuals. New types of violence require different approaches in understanding conflict. To this end, the central aim of this review is to understand and form an appreciation towards the phenomenon of conflict trauma. An in-depth systematic review was carried out with deductive inductive thematic research design to explore patterns within the paradigm of trauma studies. Themes found over the span of the last 22 years in research literature revealed that conflict trauma studies are generally centered around three basic types of trauma exposure; socio-political, gender based and transgenerational trauma. The findings indicate exposure to traumatic events in conflict affected groups underpins distinct patterns with an underlying theme of post-traumatic growth as essential to help survivors move on from the trauma. It is assumed through the analysis of this research that in some cases conflicts make communities more resilient and form an important catalyst for personal growth